2020
DOI: 10.3390/agriculture10060231
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Productive, Competitive, and Economic Aspects of Spring Cereal Mixtures in Integrated and Organic Crop Rotations

Abstract: Cultivation of spring cereal mixtures (SCMs) is one of the ways to increase the yield of crops in mountainous areas of Poland. There are only a few current long-term studies on this topic. Our study aimed at analyzing yield and competitiveness as well as the economic indicators of spring cereals in pure or mixed sowings in integrated or organic crop rotations over nine years. A field experiment including pure sowings of oats, spring barley, or spring triticale and their two-component SCMs, each in two systems,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…The recent findings confirmed the benefits of intercropping, such as increased nitrogen uptake by cereals cultivated in a mixture with legumes [1][2][3], and more efficient use of water and nutrients in soil profile [4]. Different species in the mixtures also use field space more effectively [5], i.e., in weather conditions unfavorable for the growth of one species, the companion crop usually grows better [6,7]. Mixed systems are characterized by higher yields than pure stands [3,5,7,8].…”
supporting
confidence: 55%
See 3 more Smart Citations
“…The recent findings confirmed the benefits of intercropping, such as increased nitrogen uptake by cereals cultivated in a mixture with legumes [1][2][3], and more efficient use of water and nutrients in soil profile [4]. Different species in the mixtures also use field space more effectively [5], i.e., in weather conditions unfavorable for the growth of one species, the companion crop usually grows better [6,7]. Mixed systems are characterized by higher yields than pure stands [3,5,7,8].…”
supporting
confidence: 55%
“…Different species in the mixtures also use field space more effectively [5], i.e., in weather conditions unfavorable for the growth of one species, the companion crop usually grows better [6,7]. Mixed systems are characterized by higher yields than pure stands [3,5,7,8]. Crop mixtures provide several agroecosystem services, e.g., increase biodiversity and support the diversity of beneficial insects, as well as reduce the outbreak of pests, which, among other things, is linked to decreased availability of food sources [9].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Many years of research conducted in Poland have shown that cereal mixtures (especially barley with oats) produced higher yields than pure crops of the same varieties, mainly due to an increase in the leaf area index LAI and lend equivalent ratio LER [29]. Comparing the organic management system with the integrated management system revealed that the average gross margin (less profit) was twice as high in the mixtures grown in the organic system [30]. However, when deciding to make changes in crop selection, one should take into account the consequences of decreasing the use of mixed crops, as this may hinder the implementation of self-sufficiency and land-use efficiency programs [31].…”
Section: Multicropping and Types Of Mixturesmentioning
confidence: 99%